ANALISIS STRUKTUR DAN DISTRIBUSI PENDAPATAN RUMAH TANGGA PETANI DI LAHAN RAWA LEBAK - Nasir, Nazir; Zahri, Imron; Mulyana, Andy; Yunita, Yunita (Badan Penerbitan Fakultas Pertanian, Universitas Bengkulu, 2015)
The purpose of this study are: (1) to determine the structure of the household income of rice farmers in lowland swamp land, and (2) to determine the distribution of household income of farmers in various typologies lebak. Penelitian wetlands was held in Ogan Ilir and Ogan Ogan Ilir in March until May 2013. Sampling technique is simple random sample of 222 farmers, or 10.5 percent of 2,111 respondents used in this research. These respondents were divided into 3 groups: farmers who cultivate land swampy marsh embankment, mid and deep. The method used is a survey method. Data collected consist of primary and secondary data. The structure of household income farmers viewed from the contribution of a business on total household income, while the income distribution is calculated using Gini index. The results showed the contribution of household income on lebak dikes and in largely derived from non farming, to contribute to the embankment of lebak by 63.62% and amounted to 48.43% in the lowland, while in the mid lebak largely derived from rice farming with a contribution of 70.03%. The distribution of household income in the three types of inequality lebak almost evenly with relatively low because it has a Gini index of less than 0.4.